Scientific peer review in the modern era: A comprehensive guide - Nimrat Kaur Sandhu; Rhea Wason; Ashish Goel (Indian Journal of Rheumatology)
The scientific peer review process involves scrutinizing the work of researchers by a panel of scientific experts who are selected by the journal to which they have submitted a manuscript. It ensures that only the best ideas and the highest quality of research are circulated through the publications in the scientific journals. The concept of peer review preceded the development of the scientific journal, has co-evolved with the scientific method, and has now become irreplaceably integrated with it. The traditional method of peer review involved multiple submissions and revisions and was criticized for being time-consuming and biased with the reports of professional misconduct even among the renowned journals. Several guidelines now ensure a more ethical, consistent and rigorous review process. Novel methods of review such as the use of registered reports and the dynamic review methods are also being explored by publishers to deal with these issues. Although the role of peer review as a gatekeeper for high-quality research has been well established, its value in future research is rapidly evolving. Newer methods and adherence to guidelines will go a long way in improving this imperfect pillar of science.